A Review on Evolution and Multidimensional Impacts of Green Chemistry - Rana, Rekha; Sharma, Deep; Sharma, Varun (Journal of Biomedical and Pharmaceutical Research, 2022)
Green chemistry which is the latest and one of the most researched topics now days has been in demand since 1990’s. Majority of research in green chemistry aims to reduce the energy consumption required for the production of desired product whether it may be any drug, dyes and other chemical compounds to minimize the environmental and occupational hazards inherent in industrial activities. Later, researchers discussed the importance of using twelve principles in thedevelopment of new methods and analytical techniques with the purpose of reducing their environmental impacts. Since the 1940s, social movements have revolutionized green chemistry and provided shifts in industrial positions and sustainable processes with advances in environmental impact and awareness of companies and population. One of the most active areas of Research and Development in Green Chemistry is the development of analytical methodologies, giving rise to the new concept of Green Analytical Chemistry. Green chemistry as the name indicates is a technology imbedded, environmental friendly and cost effective utilization of resources that minimize or even eliminate the production of harmful bi-products in the design and manufacturing of the product Here the impacts of green chemistry on environment, pharmaceutical analyzes, population and analyst are described. Every choice and analytical attitude has consequences both in the final product and in everything that surrounds it. This work shows a critical review of the history and evolution of green chemistry as well as its impact on pharmaceutical analysis, environment, population, analyst company and our future. Keywords: Green chemistry, Multidimensional impacts, Green analytical chemistry